Problem Based Learning Models Assisted by Mathcard on Students' Critical Thinking Abilities and Mathematical Dispositions - Firda Nur Arifa; Syita Fatih ‘Adna; Aprilia Nurul Chasanah (Pendidikan Matematika UNIMOR, 2024)
Learning using the 2013 curriculum encourages students to have 4C abilities. The findings of the initial test results in class IX of SMP Negeri 3 Muntilan, their critical thinking skills were classified as poor. Mathematical disposition abilities influence the low and high level of students' mathematical critical thinking abilities. The findings from the initial questionnaire showed that mathematical disposition ability was in the medium category. Then, with the need for students not to get bored quickly and to be active when learning, the Problem Based Learning (PBL) model assisted by math cards was implemented. The research objective to be achieved in this study is to analyze in a multivariate way the critical thinking abilities and mathematical disposition abilities taught using the PBL model assisted by mathcards are better than those taught using the expository learning model on quadratic equations. The approach used is quantitative research with a quasi experimental design in the form of a non equivalent posttest only control group design. The results of this research are; Multivariately, students' critical thinking abilities and mathematical disposition are better in the PBL model assisted by mathcards compared to the expository model in quadratic equations. However, educators need to reconsider the material that will be applied with this mathcard-assisted PBL model, because this model is not necessarily suitable for all material.